Uma metodologia para geração otimizada de ambientes virtuais baseados em usinas hidrelétricas - Moraes, Ígor Andrade (2016)
Based on the possibility of real-time interaction with three-dimensional environments through an advanced interface, Virtual Reality consist in the main technology of this work, used in the design of virtual environments based on real Hydroelectric Plants. Previous to the process of deploying a Virtual Reality System for operation, three-dimensional modeling and interactive scenes settings are very importante steps. However, due to its magnitude and complexity, power plants virtual environments generation, currently, presents high computing cost. This work aims to present a methodology to optimize the production process of virtual environments associated with real hydroelectric power plants. In partnership with electric utility CEMIG, several HPPs were used in the scope of this work. During the modeling of each one of them, the techiniques within the methodologie were addressed. After the evaluation of the computional techniques presented here, it was possible to confirm a reduction in the time required to deliver each hydroelectrical complex. Thus, this work presents the current scenario about development of virtual hydroelectric power plants and discusses the proposed methodology that seeks to optimize this process in the electricity generation sector.